2020
DOI: 10.3390/su12197901
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Religion on Sustainable Consumption: A Systematic Review and Future Research Agenda

Abstract: Background: Due to the current environmental crisis, sustainable consumption (SC) behaviour and its drivers has gained significant attention among researchers. One of the potential drivers of SC, religion, have been analysed in the last few years. The study of the relationship between religion and adoption of SC at the individual level have reached mixed and inconclusive results. Methods: Following the PRISMA guidelines, a systematic review of articles published between 1998 and 2019 was conducted using the We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 106 publications
1
26
0
2
Order By: Relevance
“…Thus, religious beliefs, ideas and practices may drive the adoption of energy consumption behaviour by fostering salient and inner motivations for behavioural change. Other studies have shown that ethnicity and religion are the most important determinants of consumer behaviour (Bailey & Sood, 1993) and more specifically, consumer ethics, evaluation of product quality, product pricing and materialism (Orellano et al, 2020). In view of this evidence, it is plausible to think that ethnicity and religion at the individual level may influence the patterns of environmental sustainability as well.…”
Section: Diversity At a Globe And Importance In Environment Sustainab...mentioning
confidence: 95%
See 3 more Smart Citations
“…Thus, religious beliefs, ideas and practices may drive the adoption of energy consumption behaviour by fostering salient and inner motivations for behavioural change. Other studies have shown that ethnicity and religion are the most important determinants of consumer behaviour (Bailey & Sood, 1993) and more specifically, consumer ethics, evaluation of product quality, product pricing and materialism (Orellano et al, 2020). In view of this evidence, it is plausible to think that ethnicity and religion at the individual level may influence the patterns of environmental sustainability as well.…”
Section: Diversity At a Globe And Importance In Environment Sustainab...mentioning
confidence: 95%
“…Among the drivers that have been receiving growing attention in the literature are ethnic and religious diversity (Amin, 2018(Amin, , 2019. It is estimated that 84% of the world's population belong to a religious group, where approximately 32% are Christians, 23% are Muslims, 15% are Hindus, 7% are Buddhists, 0.2% are Jews, 6% are folk or traditional religionists and less than 1% are people of other religions (Orellano et al, 2020). These religions are a significant source of wisdom, morality and ethics for individuals (Orellano et al, 2020).…”
Section: Diversity At a Globe And Importance In Environment Sustainab...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial results-or lack thereof-required a slight adjustment to the PRIMSA guidelines for a systematic literature review. The objective, four-stage process-selection, screening, eligibility, and articles included in analysis-has proven effective for visualizing the academic output related to various environmental issues [42,43].…”
Section: Methodsmentioning
confidence: 99%